Certain inversion and representation formulas for q-sumudu transforms - (:unkn) unknown (HACETTEPE UNIV, FAC SCI, 2014)
In the present paper, we explore the formal properties of the q-Sumudu transforms to derive a number of inversion and representation formulas. Some interesting applications of the main results are also presented in the concluding section.
Keywords: q-Laplace transforms; q-Sumudu transforms; q-Bessel functions